DI-043 Biologics are a new challenge for hospital pharmacists - pilot study of patient adherence. (24th March 2015) - Borza, E; Botz, L; Fittler, A; Juni, E; Kiss, C
Abstract : Background: Dispensing biological drugs has become an exclusive competency of hospital pharmacists both to in- and outpatients in recent years in Hungary. Biologicals are the most important treatment for patients with rheumatoid diseases, but poor adherence can undermine the effectiveness of these medicines. Although routine monitoring have been recommended, there are no standardised methods to track adherence to biologicals. Purpose: Pilot study to measure rheumatology outpatients' adherence to biologicals, to identify medicines errors, to improve storage and use so they are safe and effective and to identify critical intervention points for hospital pharmacists. Material and methods: A 31-item questionnaire using a four point Likert scale was developed based on the Rheumatology Compliance Questionnaire. Questions focused on factors modifying treatment and adherence. Patients were interviewed by a hospital pharmacist. The data were evaluated by descriptive analysis and chi-square test. Results: 106 rheumatology patients filled in our questionnaire; 21.7% of respondents were identified as non-adherent. Neither side effects (p = 0.303), therapeutic switch (p = 0.578) nor complexity of treatment (p = 0.712) correlated significantly with adherence category. Patient-centred care significantly influenced adherence (p = 0.057). A higher rate of adherence was measured amongst patients receiving an infusion in the hospital (67%), than those self-administering biologicals at home (59%, p = 0.260). Numerous medicines use errors were detected during the personal interviews. 29% of responders found patient education ineffective, 19% emphasised the lack of patient-centred care. Conclusion: Adding a pharmacist to the healthcare team has many benefits in improving adherence. Based on our findings hospital pharmacists must focus on: identification of non-adherent patients during personal interviews providing information about storage and administration of biologicals at home the elderly, who do not accept the invasive nature of administration As an outcome of our study a specific patient leaflet has been developed aiming to optimise outcomes and minimise risks of biologicals used in rheumatoid diseases. References and/or acknowledgement: No conflict of interest.